Leader Member Exchange and Managerial Skills of Madrasah Heads: A Sequential Explanatory Mixed Methods Study on Elementary Madrasah Performance - Sumaryati; Afra Pranata; Dadang; M. Nopri Arisandi Prayoga; Supriyadi; Noorseha Ayob (MIMBAR PGSD Undiksha, 2026)
Low madrasah performance is influenced by the quality of leadership relationships and the managerial skills of madrasah principals. This study aims to analyze the effect of Leader Member Exchange (LMX) and the managerial skills of madrasah principals on madrasah performance. The research employed a mixed-methods design with a sequential explanatory approach. The participants in the quantitative stage were madrasah teachers selected through a specific sampling technique. Data were collected using questionnaires and in depth interviews, with instruments in the form of Likert scales and interview guidelines. Quantitative data were analyzed using multiple regression, while qualitative data were analyzed thematically. The results show that LMX has a significant effect on madrasah performance (β = 0.684; p < 0.05), while the managerial skills of principals contribute positively but are not statistically significant in the partial test. Simultaneously, both variables significantly affect madrasah performance (F = 98.856; p < 0.001) with an R² value of 0.608, indicating that more than half of the variation in madrasah performance can be explained by these variables. The findings show that open, fair, and empathetic leadership enhances teachers’ trust, motivation, and engagement, while managerial consistency strengthens organizational effectiveness. Madrasah performance is shaped by the synergy between relational and managerial leadership, highlighting the need to strengthen principals’ emotional intelligence, participatory communication, and moral-spiritual values.